THE USE OF TWO-DIMENSIONAL AUTOCORRELATION OF VIBRATION SIGNAL FOR FAULT DETECTION OF RECIPROCATING COMPRESSORS - Widodo, Achmad; Prasojo, Satrio Budi; Haryanto, Ismoyo (ROTASI, 2016)
Reciprocating compressors are the oldest kind of compressors designed for mass production. These compressors still become- the best choice for several industrial application due to their advantages that give high compression ratio and low mass flow. There are many cases of reciprocating compressors faults, such as fault in valve, wrist-pin, and crankpin bore on connecting rod. In this paper, fault detection of such compressors due to exhaust valve and pin bore faults will be presented based on the vibration signal. At first, time domain and frequency domain will be the basic method for analysis and then it will be completed by spectrogram and two-dimensional autocorrelation. The patterns of vibration signals were analyzed and compared through their vibration signatures. Vibration signatures could give informations related to impending faults in the compressors. Therefore, the fault diagnostics of compressor could be realized